What is Gen Z Looking For? Work and Career Journey: (Study of the Phenomenon of Gen Z Alumni of Yogyakarta Universities who Work in Sleman, Yogyakarta) - Swastuti Amalia Putri; Arif Hartono (International Journal of Economics and Management Sciences, 2025)
This research discusses the meaning of work and career for Generation Z. The research was conducted using qualitative methods and a phenomenon study approach. The research was conducted in Yogyakarta by involving 5 resource persons with fulfilling criteria, namely Generation Z who are workers and work in the Sleman area, Yogyakarta and are alumni of universities in Yogyakarta. The data analysis method uses Data Triangulation, namely, data reduction, data display and conclusions. Generation Z, known as digital natives, are proficient in using technology, have high creativity, future orientation, and the ability to collaborate. Access to technology allows them to explore a variety of work options that match personal interests and values. The mismatch between work meanings often makes Gen Z less likely to stay in their jobs. The issues addressed in this study are the meaning of work, the meaning of career, and the factors that influence careers for Generation Z. The research findings show that: 1) The meaning of work for Gen Z in the findings, on job orientation, is to earn money to fulfill life needs. In career orientation, it emphasizes the importance of seeking experience, self-development, increasing social status and expanding relationships to prepare for their future careers. While in calling orientation, describing work as a form of worship and giving benefits to others. 2) The meaning of career for gen Z in the findings is a means to achieve professional advancement, apply knowledge, develop skills, and contribute to positive change. 3) Factors that influence careers include internal factors including interests, talents, and knowledge, and external factors including family, friends, social media, work environment, and boyfriend or girlfriend.